Intravenous Lidocaine Infusion for Pain Management After Laparoscopic Bariatric Surgery: A Double-Blinded, Placebo-Controlled Trial - Ali Amer; Sabreen Saleh; Ekram Rijhi (Libyan Journal of Medical and Applied Sciences, 2025)
Surgical treatment is still the sole evidence-based strategy for weight loss in patients with severe obesity (class II or III obesity). While there are a number of surgical methods, the most popular ones are laparoscopic gastric banding and gastric bypass. The growing understanding of the advantages of effective acute pain management on short-term outcomes, patient satisfaction, quality of life, and the prevention of chronic pain syndromes—a crucial factor that could otherwise jeopardize overall recovery following laparoscopic procedures—is reflected in the recent adoption of standardized criteria for pain assessment and management. There is ongoing discussion over postoperative analgesia for patients having a gastrectomy. Acetaminophen, nonsteroidal medications, bupivacaine infiltration before surgery, opioids for extreme pain, and epidural analgesia are some of the techniques utilized to manage pain following surgery. This randomized, double-blind, placebo-controlled trial was carried out at Zliten Medical Center (Zliten, Libya) and two specialized laparoscopic clinics in Tripoli, Libya, from January 2020 to June 2021, with 42 patients of both sexes. All patients were randomized into two groups: Group I received an intravenous lidocaine infusion (n = 21), while Group II received a placebo (n = 21). The study found that systemic lidocaine infusion in obese patients undergoing laparoscopic bariatric surgery was associated with lower postoperative morphine requirements, lower pain intensity as measured by VAS, longer time to first morphine request, earlier mobilization, earlier bowel movement and flatus passage, shorter ICU stay, and shorter hospital length of stay. These findings, in the absence of major problems, suggest that lidocaine infusion is a viable perioperative opioid-sparing analgesic in obese individuals.